Fluoxetine modulates neuronal activity in stress-related limbic areas of adult rats subjected to the chronic social isolation - Stanisavljević, Andrijana; Perić, Ivana; Gass, Peter; Inta, Dragos; Lang, Undine E.; Borgwardt, Stefan; Filipović, Dragana (Brain research bulletin, 2020)
Antidepressant fluoxetine (Flx) is the first therapeutic choice for the treatment of major depression (MD), however neuroanatomical spots of its action remain unclear. Immunohistochemical detection of c-Fos protein expression has been used for mapping activated neuronal circuits upon various stressors and drugs. We investigated the effect of 3 weeks of Flx treatment (15 mg/kg/day) on changes in neuronal activity, by mapping the number of c-Fos+ cells, in several brain subregions in adult male rats of control and following 3 weeks of chronic social isolation (CSIS), an animal model of depression. The aim was to identify brain subregions activated by vehicle or Flx treatment in both controls or simultaneously applied with CSIS. Flx prevented depressive- and anxiety-like behaviors in CSIS rats. In controls, Flx increased the number of c-Fos+ cells in the anterior/posterior piriform cortex (aPirCx, pPirCx), retrosplenial cortex dysgranular (RSD) and granular, c region (RSGc), dorsal hippocampal subregions (CA1d, CA2, CA3d, DGd), lateral habenula (LHB), paraventricular thalamic nucleus, posterior part (PVP) and lateral/basolateral complex of amygdala (LA/BL). CSIS-induced neuronal activation was observed in brain subregions implicated in mood and other mental disorders such as aPirCx, pPirCx, caudate putamen (CPu), acumbens nucleus shell (AcbSh), RSD, RSGc, DGd, PVP and LA/BL. Flx increased neuronal activation in both controls and CSIS rats in the CA1d, CA2, CA3d, PVP, LA/BL, while in striatum increased neuronal activation was observed only in CSIS. Our data identify activated CSIS-related brain subregions and/or Flx treatment, in which Flx increased c-Fos protein expression in CSIS rats.
Online verfügbar: 28. Juli 2020
Gesehen am 08.08.2025